Keputusan Pembelian Motor di Tinjau Dari Harga dan Promosi - Farikhul Muafiq; Aria Mulyapradana; Budi Nugraha; Aria Elshifa (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
Abstract: The purpose of this research is to find out and analyze the influence of price and promotion on motorcycle purchase decisions. The object of this research was 90 respondents from the Office Administration Study Program. The research method used is quantitative. This research data was processed using multiple linear regression tests. Htest result F obtained Fcount F 18,743 greater than Ftable 3.10. The significance value of 0.000 is also less than the probability of 0.05. So, it can be concluded that prices and promotions together (simultaneously) have an influence on the decision to buy a motorbike in students. For the efficiency result of thetermination, the Adjusted R Square value was 0.285. This value shows that the influence of price and promotion on motorcycle purchase decisions in students is 28.5% while the remaining 71.5% is influenced by other variables outside this research model. Keywords: Purchasing Decision, Price, Promotion, Motor